Immunological Properties of Murine Parthenogenetic Stem Cell-Derived Cardiomyocytes and Engineered Heart Muscle - Didié, Michael; Galla, Satish; Muppala, Vijayakumar; Dressel, Ralf; Zimmermann, Wolfram-Hubertus (Frontiers in Immunology, 2017)
Pluripotent parthenogenetic stem cells (pSCs) can be derived by pharmacological activation of unfertilized oocytes. Homozygosity of the major histocompatibility complex (MHC) in pSCs makes them an attractive cell source for applications in allogeneic tissue repair. This was recently demonstrated for pSC-based tissue-engineered heart repair. A detailed analysis of immunological properties of pSC-derived cardiomyocytes and engineered heart muscle (EHM) thereof is, however, lacking. The aim of this study was to determine baseline and cytokine-inducible MHC class I and MHC class II as well as programmed death ligand-1 (PDL-1) and co-stimulatory protein (CD40, CD80, CD86) expression in pSC-derived cardiomyocytes and pSC-EHM in vitro and in vivo. Cardiomyocytes from an MHC-homologous (H2d/d) pSC-line were enriched to ~90% by making use of a recently developed cardiomyocyte-specific genetic selection protocol. MHC class I and MHC class II expression in cardiomyocytes could only be observed after stimulation with interferon gamma (IFN-gamma). PDL-1 was markedly upregulated under IFN-gamma. CD40, CD80 and CD86 were expressed at low levels and not upregulated by IFN-gamma. EHM constructed from H2d/d cardiomyocytes expressed similarly low levels of MHC class I, MHC class II and costimulatory molecules under basal conditions. However, in EHM only MHC class I, but not MHC class II molecules were upregulated after IFN-gamma-stimulation. We next employed a co-cultivation system with MHC-matched and MHC-mismatched splenocytes and T-cells to analyze the immune stimulatory properties of EHMs. Despite MHC-mismatched conditions EHM did not induce splenocyte or T-cell proliferation in vitro. To evaluate the immunogenicity of pSC-derived cardiomyocytes in vivo, we implanted pSC-derived embryoid bodies after elimination of non-cardiomyocytes (cardiac bodies) under the kidney capsules of MHC-matched and -mismatched mice. Spontaneous beating of cardiac bodies could be observed for 28 days in the matched and for 7 days in the mismatched conditions. Teratomas formed after 28 days only in the MHC-matched conditions. Immunohistochemistry revealed single clusters of CD3-positive cells in the border zone of the implant in the mismatched conditions with few CD3-positive cells infiltrating the implant. Taken together, MHC-matched pSC-cardiomyocyte allografts show little immune cell activation, offering an explanation for the observed long-term retention of pSC-EHM allografts in the absence of immunosuppression.